2015
DOI: 10.1056/nejmoa1506362
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase Receptor and Chronic Kidney Disease

Abstract: BACKGROUND Relatively high plasma levels of soluble urokinase-type plasminogen activator receptor (suPAR) have been associated with focal segmental glomerulosclerosis and poor clinical outcomes in patients with various conditions. It is unknown whether elevated suPAR levels in patients with normal kidney function are associated with future decline in the estimated glomerular filtration rate (eGFR) and with incident chronic kidney disease. METHODS We measured plasma suPAR levels in 3683 persons enrolled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
378
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 370 publications
(403 citation statements)
references
References 40 publications
22
378
2
1
Order By: Relevance
“…Hence, suPAR affects the αvβ3 integrins pathway, resulting in the inability of podocytes to adapt to physiological events 9. This highlights a proposed mechanism behind which suPAR is involved in the development of different pathologies including chronic kidney diseases (CKD), focal segmental glomerulosclerosis (FSGS) and diabetic nephropathy (DN) 10. Two major studies with several thousands of individuals showed that plasma suPAR is associated with new onset kidney disease 10.…”
Section: Nephrologymentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, suPAR affects the αvβ3 integrins pathway, resulting in the inability of podocytes to adapt to physiological events 9. This highlights a proposed mechanism behind which suPAR is involved in the development of different pathologies including chronic kidney diseases (CKD), focal segmental glomerulosclerosis (FSGS) and diabetic nephropathy (DN) 10. Two major studies with several thousands of individuals showed that plasma suPAR is associated with new onset kidney disease 10.…”
Section: Nephrologymentioning
confidence: 99%
“…This highlights a proposed mechanism behind which suPAR is involved in the development of different pathologies including chronic kidney diseases (CKD), focal segmental glomerulosclerosis (FSGS) and diabetic nephropathy (DN) 10. Two major studies with several thousands of individuals showed that plasma suPAR is associated with new onset kidney disease 10. Higher suPAR level at baseline was associated with a greater decline in the estimated glomerular filtration rate (eGFR) during subsequent visits and was associated with incident CKD 10.…”
Section: Nephrologymentioning
confidence: 99%
“…suPAR is also a novel indicator of risk in the CKD population. A recent large study involving 3683 patients demonstrated that elevated suPAR levels were independently associated with the incidence of CKD and predicted an accelerated decline in the estimated glomerular filtration rate in groups [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Following the description of suPAR as a potential FSGS “circulating factor” came the publication of a major paper delineating a relationship between suPAR levels at baseline assessment and progression of CKD [37]. …”
Section: Role Of Supar In Progression Of Chronic Diseasementioning
confidence: 99%